Principles or rules-based regulation in the face of uncertainty - does it really matter? - Pečarič, Mirko (Lex localis, 2017)
The public administrations prepare draft laws. New things always emerge that cannot be in advance framed in laws. One solution could be the principle-based approach on the local and national level that gives the most relevant principles-rules combinations in the face of complexity. The paper presents the ability to measure principles and rules: it establishes the "1:47 rule" or ratio between the principles and rules, and gives a model that embraces the principles-rules evaluation elements and their weights. By this method, decision-makers and norms' addresses could achieve decisions without the need for more and more detailed, but ineffective regulations.
Keywords: javna uprava; pravo; upravno pravo